Parvimonas micra causing native hip joint septic arthritis - Ryan, Patrick M. (Proc (Bayl Univ Med Cent), 2021)
Parvimonas micra is a bacterium normal to oral and gastrointestinal flora that has been implicated in cases of discitis, osteomyelitis, and prosthetic joint infections, often involving dental procedures or periodontal disease. It is an extremely rare cause of infection outside of these circumstances. We describe a case of septic arthritis of the native hip joint due to P. micra.